Efektifitas Bahan Ajar Panduan Pembelajaran Kebencanaan Di Kabupaten Klaten Pada Materi Bencana Gempa Bumi Terhadap Hasil Belajar Siswa Melalui Strategi Snow Balling Di SMK N 1 Trucuk - Fahminingrum, Nurul; , Drs. Suharjo, M. S (2016)
This study aims to know the effectiveness of an integrated teaching material "Learning Guide of Disaster in Klaten Regency" particularly in the material earthquake using the snow balling strategy in SMK N 1 Trucuk. This study designed using experimental with sampling technique to the 34 students who following Disaster Prepared School extracurricular. Data analysis was performed with independen sample t test and mann whitney test ontudents learning outcome. The result from this study showed that "Learning Guide of Disaster in Klaten Regency" have been effective to be applied in learning processes.If can be proofed from the mean of post test score 85,33 in first experiment class and 78,29 in second experiment class. In students learning outcome of first and second experiment classes are already qualified for the minimum graduation criteria. According Mann Whitney analysis Ho is accepted and Ha is rejected.